2010 IEEE Sensors 2010
DOI: 10.1109/icsens.2010.5689997
|View full text |Cite
|
Sign up to set email alerts
|

Vision-based displacement sensor for monitoring dynamic response using robust object search algorithm

Abstract: This paper develops a vision-based displacement measurement system for remote monitoring of vibration of largesize structures such as bridges and buildings. The system consists of one or multiple video cameras and a notebook computer. With a telescopic lens, the camera placed at a stationary point away from a structure captures images of an object on the structure. The structural displacement is computed in real time through processing the captured images. A robust object search algorithm developed in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 14 publications
0
63
0
1
Order By: Relevance
“…Screw is an important part which is widely used in engineering and large-scale structures. As reported in [16], when the target panel is difficult to install, specific features or components, such as screws and gusset plates, can be regarded as the tracking object. Here, we take the screw as the template for tracking.…”
Section: Simulation Testmentioning
confidence: 99%
“…Screw is an important part which is widely used in engineering and large-scale structures. As reported in [16], when the target panel is difficult to install, specific features or components, such as screws and gusset plates, can be regarded as the tracking object. Here, we take the screw as the template for tracking.…”
Section: Simulation Testmentioning
confidence: 99%
“…The proposed EEM technique is robust in tracking low‐contrast features due to utilization of edge information in the form of EEM codes, which contain gradient magnitudes and orientations, rather that pixel intensities directly. Research in literature has shown similarity matching can be made robust by using pixel gradients rather than pixel intensities (Freeman and Roth, ; Kaneko et al., ; Fukuda et al., ).…”
Section: Computer Vision‐sensing System Based On Edge‐enhanced Matchingmentioning
confidence: 99%
“…The authors’ team previously developed the orientation code matching (OCM) technique, which uses gradient information of images to achieve robust displacement measurement against lighting changes in tracking artificial target (Fukuda et al., ). Upon validating its robustness in template matching against illumination change and occlusion, the OCM was further applied to measurements of bridge displacements in the field (Feng et al., ; Feng and Feng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sensors currently available for measuring structural displacements can be classified as contact‐type (e.g., linear variable differential transformer) and noncontact‐type (e.g., GPS, laser vibrometer, and radar interferometry system) sensors . The contact sensor requires physical access to structures to install the sensor and connect it to a stationary reference point, which is often difficult or even impossible to locate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these sensors need to be wired to external devices for data acquisition and power supply, making the installation even more cumbersome, time‐consuming, and costly. The GPS sensors are easier to install but the measurement accuracy is limited, usually with errors in the range of 5 mm and 10 mm . The noncontact laser vibrometer/displacement sensor is generally accurate, but it is not only costly but also has limited measurement distance (typically less than five meters) because longer distance measurement would require the use of a higher‐intensity laser beam that endangers human health .…”
Section: Introductionmentioning
confidence: 99%